Moral Hazard and Clear Conscience - Topi Miettinen (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
The paper studies theoretically how the optimal contract in the hidden-action moral hazard model is affected when an agent feels bad when not reaching a target effort set in the contract. While the presence of guilt brings the outcome closer to first-best, an effort target is not costless for the principal. In equilibrium, the agent's effort falls short of the target, inducing guilt which must be compensated by a higher financial reward. Thus, although the principal's payoff is higher, the agent receives a part of the monetary rents accruing to intrinsic motivation. This result differs markedly from previous contributions on contracting under social preference or pro-social motivation.
Keywords: C72; D82; Z13; 330; Moral Hazard; Norms; Agency; Social Preferences; Guilt; Work Ethic